Keterlibatan Orangtua Siswa Berkebutuhan Khusus Di Masa Pandemi Covid-19: Studi di Sekolah Inklusi - Hana Talita Margijanto; Weny Savitry Sembiring Pandia (Provitae: Jurnal Psikologi Pendidikan, 2022)
The role of parental involvement in the development and outcome of students with special needs is instrumental, especially during the remote learning period. However, parents are not always involved in children's learning activities at home on a regular basis, especially if they feel the students have been helped at school. This study aims to look at the involvement of parents of students with special needs at inclusive elementary school level during the remote learning period due to the COVID-19 pandemic. This quantitative study utilized a questionnaire based on the Hoover-Dempsey and Sandler parental involvement model on parents of students with special needs in Greater Jakarta. The data were interpreted using the hypothetical categorization method. The results showed that parental involvement was high, especially at home. In addition, parental role construction and perception of involvement invitation from school were high. These results show that despite the alarming pandemic condition, parental involvement remains high. This is presumably because parents still have to support their children even if they have to sacrifice their time. Suggestions are discussed to maintain the level of parental involvement and to address less ideal motivating factors.